Comparative SNR Analysis Between Instrument ADAS1000 and AD620 - Tri Arief Sardjono; Hendra Kusuma; Tasripan; Kharis Sugiarto (Jurnal Sistim Informasi dan Teknologi, 2022)
The semiconductor technology for a certain function, such as instrumentation amplifier ICs is currently developing very fast, commercially available and can be obtained easily on the market. An instrumentation amplifier is a very important part in the process of data acquisition, especially for biopotential signals from the human body because its amplitude is very small and susceptible to noise interference. The selection of the proper amplifier instrumentation will produce an accurate biopotential signal reading. This paper explains the use of 2 types of instrumentation amplifiers, namely AD620 and ADAS1000, which are used in the design and realization of 12-channel ECG (Electrocardiograph). The performance and noise resistance of the two instrumentation amplifiers are compared and analyzed so that an appropriate instrumentation amplifier can be determined especially in the case of 12-channel ECG applications. 12-channel ECG was chosen because of the complexity of the design and can provide more detailed information as well as to detect the abnormalities heart’s functions. The results shows that 12-channel ECG using AD620 instrumentation amplifier has an SNR value below 12.04 dB, while using the ADAS1000 instrumentation amplifier has an SNR value below 35.5 dB and it is more resistant to noise interference.